Impact of Work Load and Stress in Call Center Employees: Evidence from Call Center Employees - Chaudhary, Sana; Nasir, Nadia; ur Rahman, Saif; Masood Sheikh, Salman (Pakistan Journal of Humanities and Social Sciences, 2023)
The study investigates the Impact of Workload and Technologies on the Performance of Call Centre Employees." Single-way ANOVA is used for analysis. In this study, we use questionnaires to gather data on the variables Gender, Age Group (In Years), Education, Experience (In Yrs.), Daily Practice, Relational Uncertainty, Relational Distance, Opportunism, and Inter-partner incompatibility. The outcomes of the study confirm that the study observe that the significant and positive effect of workload and technologies on the performance of Call Centre Employees. It implies that when departments use the results of rational uncertainty, there are considerable differences between them. The result shows that there is positive relationship between number of hours use mobile and online libraries. However, the finding exhibit that a positive and significant associations exist between no. of hour mobile use and mobile distract. Moreover, the regression result confirms that Rational Distance, Number of hours, Age, inter partner relationship and opportunism have significant effect on job satisfaction. Furth more, the coefficient value of Age has significant effect on Inter-partner incompatibility. While the Relational Distance has insignificant effect opportunity to get a better job in this company.